Who benefits from free health insurance: Evidence from Mexico - Gabriella Conti; Rita Ginja (Institute for Fiscal Studies (IFS), 2017)
We present the first comprehensive evidence on the health impacts of the introduction and expansion of a large non-contributory health insurance program in Mexico, the Seguro Popular (SP). SP provided access to health services without co-pays to individuals with no Social Security protection. To identify the impacts of the program we use its staggered rollout across municipalities between 2002 and 2010. Our intent-to-treat estimates show that SP reduced infant mortality by 10% in poor municipalities. We are unable to detect program impacts on mortality for children ages 1-4, adults or elderly. The decline in infant mortality is driven by reductions in deaths due to perinatal conditions, congenital malformations, diarrhea and respiratory infections. Also in poor municipalities, the introduction of SP is associated with an immediate 7% increase in obstetric-related hospital admissions and with a 6% increase in hospital admissions due to diarrhea and respiratory infections among infants. The decline in infant mortality attributed to SP closes 84% of the gap in infant mortality rates between poor and rich Mexican municipalities.
Keywords: H10; I12; I13; J13; O18; 330; Health Insurance; Child Mortality; Health Care Utilization; Mexico